A Novel Method to Profile Transcripts Encoding SH2 Domains in the Patiria miniata Mature Egg Transcriptome - Lauren Bates; Emily Wiseman; Alexis Whetzel; David J. Carroll (Cells)
The critical mechanism to restart zygote metabolism and prevent polyspermy during fertilization is the intracellular Ca2+ increase. All of the signaling molecules leading to the Ca2+ rise are not fully known in any species. In the sea star Patiria miniata, SFK1, SFK3, and PLCγ participate in this fertilization Ca2+ increase. These proteins share common regulatory features, including signaling via tyrosine phosphorylation and their SH2 domains. In this study, we explore two different bioinformatic strategies to identify transcripts in the Patiria miniata mature egg transcriptome (Accession PRJNA398668) that code for proteins possessing an SH2 domain. The first identified the longest open reading frame for each transcript and then utilized similarity searching tools to provide identities for each transcript. The second, novel, method involved a six-frame translation of the entire transcriptome to identify SH2 domain-containing proteins. The identified transcripts were aligned against the NCBI non-redundant database and the SwissProt database. Eighty-two transcripts that encoded SH2 domains were identified. Of these, 33 were only found using the novel method. This work furthers research into egg activation by providing possible target proteins for future experiments and a novel method for identifying specific proteins of interest within a de novo transcriptome.